Utilization of Maternal Health Care Services in Tamil Nadu - R.Ramachandran; S.Gnanalakshmi (PT FORMOSA CENDEKIA GLOBAL, 2022)
The utilization of health care services depends upon the socio-economic status of the population, the severity of disease, the availability, accessibility, and affordability of health care services. The primary, secondary, and tertiary health care delivery systems are being revamped and fine-tuned in such a way that health care is delivered efficaciously to the people at the bottom of the economic pyramid. Three rounds of District Level Household and Facility Surveys (DLHS) have been undertaken by the Ministry of Health and Family Welfare, Government of India in the past (Round-I in 1998-99, Round-II in 2002-04, and Round-III in 2007-08) with the main objective to provide reproductive and child health-related database at the district level in India. The Ministry of Health and Family Welfare, Government of India, later initiated the process of conducting DLHS-4 during 2011-2012 and designated the International Institute for Population Sciences (IIPS) as the nodal agency to carry out the survey. The present study was undertaken based on DLHS-3 and DLHS-4 surveys of Namakkal district for comparative purposes with secondary data. The literacy status of mothers was significantly associated with the level of services availed by them. On many crucial aspects of health care services, there has been a manifold increase from DLHS-3 to DLHS-4. At the same time, it is essential to focus more intensively on other areas. Thus, there is a need and scope for more focused information, education, and communication efforts towards antenatal and postnatal services provided to mothers, especially in rural areas in the Namakkal district.